Lettering : a reference manual of techniques. - Haslam, Andrew, ....- (London : Laurence King Publishing, 2011)
Using a combination of explanatory text, step-by-step photographs and classic and contemporary examples, this unique survey brings together over 80 processes involved in creating lettering and applying it to surfaces. Included are hand-drawn lettering techniques (from sign writing to tattooing); dimensional lettering (hand engraving to laser cutting); typesetting (from letterpress to lettering in food); printing (Letraset to printing on bank notes); lettering on textiles (embroidery to flag-making); and illuminated type (neon signage to holography).
Keywords: Letters; Typografie